Home » Blog » Verify that e-x2 = ∑ ((-1)n x2n) / n!

Verify that e-x2 = ∑ ((-1)n x2n) / n!

Assuming that e^{-x^2} has a power-series representation in terms of powers of x, verify that it has the form

    \[ e^{-x^2} = \sum_{n=0}^{\infty} \frac{(-1)^n x^{2n}}{n!} \]

valid for all real x.


We know the expansion

    \[ e^x = \sum_{n=0}^{\infty} \frac{x^n}{n!} \]

valid for all real x. So in this case have,

    \begin{align*}  e^{-x^2} &= \sum_{n=0}^{\infty} \frac{(-x^2)^n}{n!} \\[9pt]  &= \sum_{n=0}^{\infty} \frac{(-1)^n x^{2n}}{n!}, \end{align*}

valid for all x \in \mathbb{R}.

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):